Best of my love [large type] - Mallery, Susan (Mallery, Susan. Fool's gold., 2016)
"To overcome her painful past, baker Shelby Gilmore goes on the hunt for a friend - a male friend - to convince her stubborn psyche that men can be trusted. But where in a town as small as Fool's Gold will the petite blonde find a guy willing to not date her? Dark, charming Aidan Mitchell puts the "adventure" in Mitchell Adventure Tours ... and into the beds of his many willing female tourists. Until he realizes he's inadvertently become that guy - the one-night Casanova - and worse, everyone in town knows it. Maybe Shelby's boy/girl experiment will help him see women as more than just conquests so he can change his ways and win back his self-respect"--Page [4] cover.